Influence of Indoleamine-2,3-Dioxygenase and Its Metabolite Kynurenine on γδ T Cell Cytotoxicity against Ductal Pancreatic Adenocarcinoma Cells - Hannah Jonescheit; Hans-Heinrich Oberg; Daniel Gonnermann; Martin Hermes; Vjola Sulaj; Christian Peters; Dieter Kabelitz; Daniela Wesch (Cells, 2020)
Background: Pancreatic ductal adenocarcinoma (PDAC) is a malignant gastrointestinal disease. The enzyme indoleamine-2,3-dioxgenase (IDO) is often overexpressed in PDAC and its downstream metabolite kynurenine has been reported to inhibit T cell activation and proliferation. Since γδ T cells are of high interest for T cell-based immunotherapy against PDAC, we studied the impact of IDO and kynurenine on γδ T cell cytotoxicity against PDAC cells. Methods: IDO expression was determined in PDAC cells by flow cytometry and Western blot analysis. PDAC cells were cocultured with γδ T cells in medium or were stimulated with phosphorylated antigens or bispecific antibody in the presence or absence of IDO inhibitors. Additionally, γδ T cells were treated with recombinant kynurenine. Read-out assays included degranulation, cytotoxicity and cytokine measurement as well as cell cycle analysis. Results: Since IDO overexpression was variable in PDAC, IDO inhibitors improved γδ T cell cytotoxicity only against some but not all PDAC cells. γδ T cell degranulation and cytotoxicity were significantly decreased after their treatment with recombinant kynurenine. Conclusions: Bispecific antibody drastically enhanced γδ T cell cytotoxicity against all PDAC cells, which can be further enhanced by IDO inhibitors against several PDAC cells, suggesting a striking heterogeneity in PDAC escape mechanisms towards γδ T cell-mediated anti-tumor response.